PHENOLOGY, PLANT GROWTH AND FLORAL SYNCHRONY OF THE PARENTAL LINES OF H-374C QPM MAIZE HYBRID - Noriega González Luis Alberto; Preciado Ortiz, Ricardo Ernesto; Andrio Enríquez Enrique; Terrón Ibarra Arturo Daniel; Covarrubias Prieto, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
The temperature is a climatic parameter with the greatest influence on plants physiology; on the other hand, in maize (Zea mays L.) seed production, phenological characterization of progenitors based on heat units, defines the exact date of planting to achieve floral synchrony in hybrids formation. The objective of this research was to study the effect of temperature on growth and development stages of the trilinear hybrid progenitors of maize QPM H-374C, which determine the flower matching and seed production. The genetic material used was: the single-cross female parent (CML 176∗CML 142), their inbred lines progenitor (CML 176 and CML 142) and inbred line CML 186, male parent of H-374C. The research was conducted under irrigation during the spring-summer 2007 in Celaya, Guanajuato, Mexico. A randomized complete block design with three replications was used. The phenological stages determined with the residual method, were: f loral differentiation, tasseling, male and female flowering and physiological maturity. For growth analysis dry matter samples were taken weekly, when the plant showed four ligulated leaves and until physiological maturity. It was observed that simple cross was precocious to flowering with respect to parental lines, but the grain filling stage was longer. Floral synchrony between female parent (CML 176∗ CML 142) and male parent (CML 186) was high, while in order to form the single-cross CML 176∗CML 142, the female parent required 30 degree days of development (two days) more than the male parent to silking. The single-cross female parent expressed heterosis in leaf area, biomass, leaf area index and leaf area duration. This vigor and prolonged grain filling period reflected higher seed yield.